Xylanase VmXyl2 is involved in the pathogenicity of Valsa mali by regulating xylanase activity and inducing cell necrosis - Cui, Xinyue; Li, Xinke; Li, Shen; Huang, Yan; Liu, Na; Lian, Sen; Li, Baohua; Wang, Caixia (Frontiers in Plant Science, 2024)
Xylanase plays a key role in degrading plant cell wall during pathogenic fungi infection. Here, we identified a xylanase gene, VmXyl2 from the transcriptome of Valsa mali and examined its function. VmXyl2 has highly elevated transcript levels during the infection process of V. mali, with 15.02-fold increase. Deletion mutants of the gene were generated to investigate the necessity of VmXyl2 in the development and pathogenicity of V. mali. The VmXyl2 deletion mutant considerably reduced the virulence of V. mali in apple leaves and in twigs, accompanied by 41.22% decrease in xylanase activity. In addition, we found that VmXyl2 induces plant cell necrosis regardless of its xylanase activity, whereas promoting the infection of V. mali in apple tissues. The cell death-inducing activity of VmXyl2 dependent on BRI1-associated kinase-1 (BAK1) but not Suppressor of BIR1-1 (SOBIR1). Furthermore, VmXyl2 interacts with Mp2 in vivo, a receptor-like kinase with leucine-rich repeat. The results offer valuable insights into the roles of VmXyl2 in the pathogenicity of V. mali during its infection of apple trees.